2018
DOI: 10.30880/jtet.2018.10.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Career Decision-Making Competence, Self-Knowledge, and Occupational Exploration: A Model for University Students

Abstract: Confirmatory Factor Analysis AMOS was used to obtain the best-fit measurement models from the variables. Structural Equation Modelling (SEM) was used to test the hypotheses. The findings show that there are significant relationships between self-knowledge (SK) and career decision-making (CDM), and occupational exploration (OE) and career decision-making (CDM). The result for testing invariance of a structural model for multi-group analysis showed a validation model of self-knowledge (SK), occupational explorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This research also determines that the relationship between CDSE and Vocational Identity surpasses the socio-cultural aspect because self-belief is important for humans regardless of their races. The study of Abdullah et al (2018) shows that it is important to have self-efficacy in order for them to know about their vocational identity. This self-efficacy is important for students to make important decision in deciding on their vocational identity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This research also determines that the relationship between CDSE and Vocational Identity surpasses the socio-cultural aspect because self-belief is important for humans regardless of their races. The study of Abdullah et al (2018) shows that it is important to have self-efficacy in order for them to know about their vocational identity. This self-efficacy is important for students to make important decision in deciding on their vocational identity.…”
Section: Discussionmentioning
confidence: 99%
“…Past research conducted in Malaysia found that Malaysian students are generally good in terms of academic achievements, but seem to be lacking in other skills, such as survival and critical thinking as well as frequently showing much insecurities about their abilities. A research conducted by Abdullah et al (2018) identified important associations between self-knowledge and work-related search with career decision-makings. Another research by Sumari et al (2019) focuses mostly on the role of family functioning on career decision-making self-efficacy.…”
Section: Study Contextmentioning
confidence: 99%
“…The findings of the study by Abdullah et al (2018) & Makki et al (2015 found that most Malaysian graduates lack self-assurance, pessimistic, and lack of sufficient skills to enter for employment. Besides, graduates are considered less committed to exploring real-world work.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Moreover, through competition, an individual will be able to demonstrate their ability to others. In this case, a study by Abdullah et al (2018) also indicated that when student builds up self-knowledge like feel proud of themselves and believe can do things better than others, they can create more confident to compete well in making a career decision. Thus, competitiveness is one of the positive motivational factors that can enhance individual self-esteem towards goal achievement.…”
Section: Table 1 Cronbach's Alpha Values By Variablesmentioning
confidence: 99%
See 1 more Smart Citation